A clinical Assessment of the modified technique for extraction of abuccally carious erupted lower wisdom teeth (Mustansiria Dental Journal, 2018)
Benefit of A modified technique of extraction for buccally carious lower wisdom teeth was Assessed in (25) cases In 16 (64%) of cases it was successful and failed In 9 (36%) of the cases the technique gave a good help in avoided the need for a surgical extraction of those teeth, although it require an experience dental handed. Technique need to be studied on a wider group of cases